Gender Differences in the Influence of Family Background on Internet Addiction and Environmental Behaviour: Does Islamic Elementary School Matter? - Syarifah Salmah; Nur Inayah Syar; Rahmad; Ahmad Juhaidi (Badan Litbang dan Diklat Kementerian Agama RI, 2025)
Pro-environmental behaviour is a critical global issue across all sectors, including education. This study examines how family socioeconomic background influences internet addiction and pro-environmental behaviour among elementary school students, investigates the effects of school type and grade level, and explores gender as a moderating variable in these relationships. Using a quantitative approach with Partial Least Squares Structural Equation Modeling (PLS-SEM), data were collected from 210 parents (150 females, 60 males) through convenience sampling. The findings reveal that family economic status and family structure significantly and positively influence children's internet addiction, with students from affluent and two-parent families being more prone to smartphone or internet overuse. Internet addiction, in turn, has a significant negative impact on students’ pro-environmental behaviour. The effect of maternal education on pro-environmental behaviour is more pronounced among male students, whereas family economic status has a stronger influence on female students.. Islamic education was found to have no significant effect on either internet addiction or pro-environmental behaviour. This study contributes to the theoretical discourse in Islamic education and offers practical implications for curriculum and instructional development within Islamic educational settings. ABSTRAK Perilaku pro-lingkungan merupakan isu global yang penting di berbagai sektor, termasuk pendidikan. Penelitian ini bertujuan untuk mengkaji pengaruh latar belakang sosial ekonomi keluarga terhadap kecanduan internet dan perilaku pro-lingkungan pada siswa sekolah dasar, meneliti pengaruh jenis sekolah dan tingkat kelas, serta mengeksplorasi peran moderasi gender dalam hubungan-hubungan tersebut. Penelitian ini menggunakan pendekatan kuantitatif dengan metode Partial Least Squares Structural Equation Modeling (PLS-SEM). Data diperoleh dari 210 orang tua siswa (150 perempuan, 60 laki-laki) melalui teknik convenience sampling. Hasil penelitian menunjukkan bahwa status ekonomi dan struktur keluarga secara signifikan dan positif memengaruhi kecanduan internet pada anak. Siswa dari keluarga mampu dan keluarga dengan dua orang tua cenderung lebih rentan terhadap kecanduan smartphone atau internet. Kecanduan internet secara signifikan berdampak negatif terhadap perilaku pro-lingkungan siswa. Perilaku pro-lingkungan siswa perempuan lebih dipengaruhi oleh status ekonomi keluarga dan sedangkan pengaruh pendidikan ibu lebih besar pada siswa laki-laki. Pendidikan Islam tidak ditemukan berpengaruh signifikan terhadap kecanduan internet maupun perilaku pro-lingkungan. Temuan ini memberikan kontribusi teoretis bagi literatur pendidikan Islam dan menawarkan implikasi praktis bagi pengembangan kurikulum dan pembelajaran di lingkungan pendidikan Islam.